2020
DOI: 10.3390/ijms21020682
|View full text |Cite
|
Sign up to set email alerts
|

STVNa Attenuates Isoproterenol-Induced Cardiac Hypertrophy Response through the HDAC4 and Prdx2/ROS/Trx1 Pathways

Abstract: Recent data show that cardiac hypertrophy contributes substantially to the overall heart failure burden. Mitochondrial dysfunction is a common feature of cardiac hypertrophy. Recent studies have reported that isosteviol inhibits myocardial ischemia-reperfusion injury in guinea pigs and H9c2 cells. This work investigated the protective mechanisms of isosteviol sodium (STVNa) against isoproterenol (Iso)-induced cardiac hypertrophy. We found that STVNa significantly inhibited H9c2 cell and rat primary cardiomyocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…22,23 In addition, our previous studies also demonstrated that STVNa significantly inhibited H9c2 cell and rat primary cardiomyocyte cell surface, restored MMP and morphological integrity, and decreased the expression of mitochondrial function-related proteins fission 1 and dynamin-related protein 1. 24 Therefore, from what has been discussed above, STVNa may be more targets for drugs. On the other hand, STVNa improved the heart function by increasing cardiac contractility and decreasing cardiac stiffness without changing intracellular Ca 2+ concentration or increasing oxygen requirement.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…22,23 In addition, our previous studies also demonstrated that STVNa significantly inhibited H9c2 cell and rat primary cardiomyocyte cell surface, restored MMP and morphological integrity, and decreased the expression of mitochondrial function-related proteins fission 1 and dynamin-related protein 1. 24 Therefore, from what has been discussed above, STVNa may be more targets for drugs. On the other hand, STVNa improved the heart function by increasing cardiac contractility and decreasing cardiac stiffness without changing intracellular Ca 2+ concentration or increasing oxygen requirement.…”
Section: Discussionmentioning
confidence: 95%
“…For instance, Isosteviol ameliorates diabetic cardiomyopathy in rats by inhibiting ERK signalling pathways and inhibit the production of reactive oxygen species (ROS) and mitochondrial membrane potential (MMP) 22,23 . In addition, our previous studies also demonstrated that STVNa significantly inhibited H9c2 cell and rat primary cardiomyocyte cell surface, restored MMP and morphological integrity, and decreased the expression of mitochondrial function‐related proteins fission 1 and dynamin‐related protein 1 24 . Therefore, from what has been discussed above, STVNa may be more targets for drugs.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Isosteviol (IST) is a bioactive diterpenoid extracted by Stevia rebaudiana that has a variety of biological activities targeted at the CVS, including anti-hypertensive, anti-hyperglycemic, antioxidant, and anti-inflammatory effects [ 129 ]. In cardiomyoblasts subjected to simulated IR or pro-hypertrophic injuries, IST restored mitochondrial membrane potential, morphological integrity, and biogenesis; decreased ROS levels; and upregulated the expression of antioxidant enzymes [ 130 , 131 ]. In addition, IST relieved IR injury in rodent hearts and isolated pig hearts [ 132 , 133 ].…”
Section: Mitochondria-targeting Of Natural Compounds With Pleiotromentioning
confidence: 99%